Impact of motor interventions oriented by mastery motivational climate in fundamental motor skills of children: A systematic review - Bandeira,Paulo Felipe Ribeiro (2017)
The domain and maintenance of fundamental motor skills are essential for acquisition of more complex skills that are used in sport activities. The aim of this study was review systematically the experimental and quasi-experimental studies which implemented the mastery motivational climate in motor interventions and verify impact in fundamental motor skills of children. A search without language and date restrictions in eight databases was realized. Motor intervention studies that used the mastery motivational climate with focus in strategy for optimize the locomotors and object control skills performance in children 3 to 10 year-old were included. The evaluate of methodological quality was realized by two independents reviewers. Six papers that described motor interventions oriented by mastery motivational climate were included. The participants were children with identified motor delay, with or without cognitive or motor disabilities. All the studies indicated positive effect of intervention programs in locomotor and object control skills. The mastery motivational climate is an efficient methodological proposal teaching to promote development of locomotors and object control skills in children with motor delay.